Fundamental Characterization Techniques: Impedance and Modulus Spectroscopy - Sharma U.; Pawar V.; Singh P. (My University, 2025)
Impedance spectroscopy (IS) is one of the effective experimental techniques employed for investigating the electrical characteristics of materials and systems over a broad range of frequencies. Its adaptability makes it invaluable in numerous fields, including electrochemistry, material science, electronics, and biophysics. This technique is used to study the dynamics of bound and mobile charges within the bulk or interfacial regions of diverse solid and liquid materials like ionic, mixed ionic-electronic, semiconducting, and dielectrics. By analyzing the electrical response over a range of frequencies, these techniques provide valuable insights into the materials’ electrical properties, conductivity, dielectric behavior, and other relevant parameters. Modulus (M) is one of the important measured quantities related to impedance (Z) to study the small signal measurement with respect to frequency and known as modulus spectroscopy. These are interconnected like— Complex impedance, Z∗=Z′-iZ″=1iωC0ε∗ Electric Modulus M∗=M′+iM″=1/ε∗, where, ω = 2πf. For the study of electro-ceramics complex Z∗ and M∗ are mostly used. In a polycrystalline ceramic, for the study of grains, grain boundaries, and electrodes, these can be represented by the equivalent circuit in which Resistors (R) and Capacitors (C) are connected in parallel. Consequently, in a polycrystalline electroceramic, both the properties, the dielectric and electrical, have contributions from bulk or grains, grain boundaries, and electrode polarization. This chapter will commence by providing an introduction to the fundamentals of impedance and modulus spectroscopy, followed by an explanation of impedance in electrical circuits. Further, we’ll discuss the Jonscher’s Power law, Nyquist, and Bode plot representation of the impedance/modulus of an electrical circuit. In the concluding section of this chapter, we will delve into some examples that are closely related to both spectroscopy techniques. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.